The neglected challenge: Vaccination against rickettsiae. - Anke Osterloh (Public Library of Science (PLoS), 2020)
Over the last decades, rickettsioses are emerging worldwide. These diseases are caused by intracellular bacteria. Although rickettsioses can be treated with antibiotics, a vaccine against rickettsiae is highly desired for several reasons. Rickettsioses are highly prevalent, especially in poor countries, and there are indications of the development of antibiotic resistance. In addition, some rickettsiae can persist and cause recurrent disease. The development of a vaccine requires the understanding of the immune mechanisms that are involved in protection as well as in immunopathology. Knowledge about these immune responses is accumulating, and efforts have been undertaken to identify antigenic components of rickettsiae that may be useful as a vaccine. This review provides an overview on current knowledge of adaptive immunity against rickettsiae, which is essential for defense, rickettsial antigens that have been identified so far, and on vaccination strategies that have been used in animal models of rickettsial infections.